2007
DOI: 10.1107/s1600536807058874
|View full text |Cite
|
Sign up to set email alerts
|

Carbonylchlorido[tris(2-aminoethyl)amine]ruthenium(II) chloride

Abstract: In the monocationic octahedral complex, [RuCl(C6H18N4)(CO)]Cl, the ruthenium(II) centre is coordinated by a chloride and a carbonyl ligand and by the tetradentate tris(2‐aminoethyl)amine (tren) chelator. The complex has approximate non‐crystallographic Cs symmetry. In the crystal structure, N—H...Cl hydrogen bonds are found, mainly with the chloride counter‐ion as the acceptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…[5][6][7] Ru(II) and Ru(III) tripodal amine complexes, especially those of imidazole-based ligands, have been studied for their anti-tumor properties [8] and, in cases where the ligand has π-acceptor groups, such compounds have drawn attention because of their luminescence and redox properties. Oddly, however, some classical coordination compounds of ruthenium with simple multidentate amines appear to be underrepresented in the literature; with tris(2-aminoethyl)amine (Tren), only one Ru(II)-Tren complex [9] and two Ru(III)-Tren [10] complexes having been reported previously (the former during our execution of this work). In this study, and Ru(DMSO) 4 Cl 2 as starting complexes, the first having recently been demonstrated to be a useful synthesis intermediate [11,12] .…”
Section: Introductionmentioning
confidence: 86%
“…[5][6][7] Ru(II) and Ru(III) tripodal amine complexes, especially those of imidazole-based ligands, have been studied for their anti-tumor properties [8] and, in cases where the ligand has π-acceptor groups, such compounds have drawn attention because of their luminescence and redox properties. Oddly, however, some classical coordination compounds of ruthenium with simple multidentate amines appear to be underrepresented in the literature; with tris(2-aminoethyl)amine (Tren), only one Ru(II)-Tren complex [9] and two Ru(III)-Tren [10] complexes having been reported previously (the former during our execution of this work). In this study, and Ru(DMSO) 4 Cl 2 as starting complexes, the first having recently been demonstrated to be a useful synthesis intermediate [11,12] .…”
Section: Introductionmentioning
confidence: 86%